Genotyping of Enterocytozoon bieneusi and Subtyping of Blastocystis in Cancer Patients: Relationship to Diarrhea and Assessment of Zoonotic Transmission - Zhang, Weizhe; Ren, Guangxu; Zhao, Wei; Yang, Ziyin; Shen, Yujuan; Sun, Yihua; Liu, Aiqin; Cao, Jianping (Frontiers in Microbiology, 2017)
Enterocytozoon bieneusi (E. bieneusi) and Blastocystis are common pathogens responsible for diarrhea in humans, especially in immunocompromised individuals. The number of cancer patients has been increasing and diarrhea is a common clinical symptom in the treatment of cancers. To understand the prevalences and genotypes/subtypes of E. bieneusi and Blastocystis in cancer patients in China, to track the infection sources, and to explore the relationships between E. bieneusi and Blastocystis infections and diarrhea, 381 fecal specimens were collected from cancer patients. Each of them was analyzed for the presence of E. bieneusi and Blastocystis by PCR amplifying and sequencing the ITS region of the rRNA gene and the barcode region of the SSU rRNA gene, respectively. 1.3% and 7.1% of cancer patients were positive for E. bieneusi and Blastocystis, respectively. No statistical differences were observed in the infection rates between the groups by age, gender and residence. E. bieneusi and Blastocystis were both significantly more common in cancer patients with diarrhea, and significant relationship of Blastocystis to diarrhea was found in chemotherapy group. Two E. bieneusi genotypes (D and a novel one named as HLJ-CP1) and two Blastocystis subtypes (ST1 and ST3) were identified with three novel ST1 sequences. This is the first report of occurrence and molecular characterizations of E. bieneusi and Blastocystis in cancer patients in China. E. bieneusi genotype D and Blastocystis ST1 and ST3 have been identified in humans and animals while one novel E. bieneusi genotype falling into zoonotic group 1, implying a potential of zoonotic transmission.